Analysis of Patient Service Quality Using the Importance Performance Analysis Method at Community Health Center - Bakhtiar Bakhtiar; Trisna Trisna; Adila Andriani (Malikussaleh University, Aceh, Indonesia, 2025)
Community Health Centres, as primary-level health service units, are responsible for providing a range of services, including health promotion, disease prevention, treatment, and rehabilitation. This study aimed to determine the level of significance and patient satisfaction with the performance of the Community Health Centre's services, as well as the priority of attributes in meeting patient needs for quality of service at the community health centre. We used the Importance Performance Analysis method to identify service attributes considered important by patients and evaluate how well these attributes are implemented. The problem in this study was patient complaints about services, such as in terms of patient examinations, incomplete information to patients, and a lack of complete medicines. The stages of this research include identifying service quality attributes, developing a questionnaire, collecting data, analysing the data, interpreting the results, and making recommendations for service improvements. The results showed 20 attributes found in the needs of community health centre patients, which were manifested in five dimensions of service, namely tangibles, reliability, responsiveness, assurance, and empathy, which were distributed to 71 predetermined samples. Based on the results of data analysis, it was found that there were six primary priority sequences in improving the quality that needed to be carried out by the community health center based on the Importance Performance Analysis method, namely, the pharmacy has a complete collection of drugs, patient experts examine patients seriously, community health center medical personnel provide the required data effectively, officers receive and serve well, Health center officers are always patient in handling patient complaints, officers’ readiness to apologize for what happened.